Service Quality Analysis of Goods Delivery Services Using the Servqual Method - Zulfiasari, Rahmarida Dwina; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to identify the level of customer satisfaction with service quality based on service quality attributes and provide recommendations for improvements to service quality attributes that are most influential in the process of improving JNE Ekspress Hub Pajajaran Malang City services. This type of research is quantitative with a descriptive approach. This research uses a sample of 100 respondents who are at least 18 years old, have used the services of JNE Ekspress Hub Pajajaran Malang City, and live in Malang City. The sampling technique used non-probability sampling with purposive sampling method. The data collection method in this study used a questionnaire measured on a Likert scale. The research instrument test used is validity and reliability test. Data testing is done using the SERVQUAL method. The results of this study indicate that all service quality attributes are negative, which indicates that the perceived value is lower than the expected value given by the respondent. This shows that the service provided by JNE Ekspress Hub Pajajaran Malang City is not in accordance with customer wishes.